Synthesizing Novel Vanillin-Based Di-Schiff Compounds and Evaluating Their Antibacterial Properties (Open Herald: Periodical of Methodical Research, 2024)
Vanillin, a phenolic aldehyde, plays a crucial role as an antimicrobial agent and holds significance in medicinal applications. This study aims to synthesize a novel vanillin compound and investigate its potential as an antibacterial agent. New di-Schiff compounds were synthesized through the reaction of vanillin with benzocaine, followed by the conversion of the ester group into a hydrazide through a reaction with hydrazine hydrate. The resulting hydrazide was involved in reactions with various carbonyl compounds to produce di-Schiff bases. Characterization of the new di-Schiff base compounds were conducted using FTIR, 1H-NMR, and 13C-NMR techniques. Subsequently, their biological activities against two types of bacteria, namely gram-positive and gram-negative, were studied. The results revealed the synthesis of five di-Schiff base compounds, confirmed through FTIR, 1HNMR, and 13C-NMR analyses. The antibacterial activity of these compounds demonstrated high efficacy against Staphylococcus aureus and E. Coli, with inhibition zones ranging from 15 to 21 mm for both bacterial types. In conclusion, this study highlights the significant antibacterial properties of the five new di-Schiff base compounds